Peran Orang Tua Untuk Meningkatkan Kemampuan Anak Dalam Membaca Al-Qur`An - Sawiyah; Mashdaria Huwaina; Anggi Septia Nugroho; Khoironi; M. Sholihin (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The activity of learning to recite the holy book Al-Qur'anul Karim is an essential component in the formation of morals and character. The involvement of guardians as companions in the Qur'anic learning process has a major influence on children's ability to read the holy book. This case explores the role of parents in improving children’s ability to read Al-Qur'anul Karim at TPA Majma’ul Aulad. The main emphasis of the research is the importance of Qur'anic education in moral development and the growth of TPA as a non-formal educational institution. The focus is on identifying the influence of parental participation, including motivation, understanding, and support provided, both at home and at the TPA. This study uses a descriptive qualitative approach with a case study method that includes direct interviews, direct observations, and document analysis. Participants consist of active students' parents and educators at the TPA. Data were processed through reduction, narrative structuring, and conclusion drawing. The findings reveal that the involvement of guardians has a rapid effect on improving children’s Qur’anic reading ability. Forms of involvement include supervision, provision of learning facilities, encouragement, and enrollment of children in the TPA. Children of active parents tend to become fluent more quickly in reading Al-Qur'anul Karim. Family and TPA collaboration plays a significant role in Qur’anic development in Indonesia.